Yerba Mate (Ilex paraguariensis) modulates NF-kappaB pathway and AKT expression in the liver of rats fed on a high-fat diet. (December 2014) - Fujii, Tatiane Mieko de Meneses; Jacob, Patrícia Silva; Yamada, Monica; Borges, Maria Carolina; Norde, Marina Maintinguer; Pantaleão, Lucas Carminatti; Oliveira, Daniela Moura de; Tirapegui, Julio; Castro, Inar Alves de; Borelli, Primavera; Fock, Ricardo Ambrósio; Rogero, Marcelo Macedo
Abstract To investigate the effect of Yerba Mate (YM) aqueous extract intake on the NF-kB pathway and AKT expression in the liver, muscle, and adipose tissue of rats submitted to a high-fat diet (HFD). Male Wistar rats were fed a control (CON) (n = 24) or a HFD (n = 24) for 12 weeks. Afterwards, rats received YM daily (1 g/kg body weight) for 4 weeks. Intake of YM aqueous extract reduced body weight gain (p < 0.05) and total blood cholesterol (p < 0.05) in the HFD group in comparison to the non-treated HFD group. HFD group demonstrated an increased glycemic response at 5 and 10 min after insulin injection. YM decreased the ratio between phosphorylated and total kinase inhibitor of κB (IKK), increased the ratio of phosphorylated to total form of protein kinase B (AKT) and reduced NF-κB phosphorylation in the liver of the HFD group. Our data suggest a beneficial role of YM in improving metabolic dysfunctions induced by HFD.